The Effect of Wood Type on the Reflection of a Table Tennis Ball - Bayu Septa Martaviano Triaiditya; Gatut Rubiono; Danang Ari Santoso (IKIP Budi Utomo Malang, 2021)
The table tennis game table can be made of any material with certain bounce height requirements according to ITTF regulations. Wood as the main material for the table is found in Indonesia. Various types of wood have the potential to be a dining table material. This study was conducted to determine the effect of the type of wood on the bounce of a table tennis ball. Experiments were carried out on 9 types of wood, namely hardwoods (teak, sono, coconut), medium hardwoods (meranti, plywood and jackfruit) and soft woods (waru, randu and sengon). The height of the falling ball is determined to be 30 cm for the ball's bounce recorded by the camera. The ball used is a ball with a weight of 24 grams and 30 grams. Camera recording data is processed with Kinovea 08.15 to get the reflection height. The bounce height is used as a reference for ITTF standard compliance. The initial height and reflection height were then used to calculate the coefficient of restitution (COR). Data collection was carried out 5 times and the average value was calculated. The level of wood hardness is influenced by its specific gravity. Hard wood has a relatively high specific gravity. Teak wood which is relatively hard has a specific gravity value of 0.59 – 0.82 gr/cm3